Implementasi Blockchain Pada Akuntansi dan Audit di Indonesia - Pratiwi, Lady Liesdyana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Since 2009, blockchain has become a potentially transformative information technology that is expected to be as revolutionary as the Internet. Originally developed as a methodology for recording cryptocurrency transactions, the functionality of the blockchain has grown into a large number of applications, such as banking, financial markets, insurance, voting systems, lease contracts, and government services. Despite such advances, the application of blockchain accounting and assurance is still unexplored. This paper aims to provide an initial discussion of how blockchain can enable a real-time, verifiable and transparent accounting ecosystem. In addition, blockchain has the potential to change current auditing practices, resulting in a more precise and timely automated audit system.